In situ and ex situ conservation gap analyses of crop wild relatives from Northeast Africa - Aldow, Ahmed; Brehm, Joana Magos; Gaisberger, Hannes; Maxted, Nigel (Springer, 2025)
Crop Wild Relatives (CWR) are wild plant taxa closely related to domesticated crops that play a vital role in enhancing crop resilience. This study assessed the conservation status of 97 priority CWR in Northeast Africa through a comprehensive approach, incorporating ecogeographic data and complementarity analysis. The analysis of 4551 occurrence records from 57 CWR highlighted significant gaps in in situ conservation. Notably, the highest number of occurrence records within Protected Areas (PAs) were found in Ethiopia, particularly in Borena National Park, Kafa UNESCO-MAB Biosphere Reserve, and Bonga National Forest Priority Area. However, only 40 taxa (~ 42%) were identified within existing PAs, with Solanum campylacanthum Hochst. cx A. Rich, and Coffea arabica L. being the most prevalent. Ecogeographic Land Characterization (ELC) maps identified 45 distinct ecological zones representing the region’s diverse habitats. Ex situ analysis revealed 1295 occurrence records from 52 taxa (54%) conserved in genebanks, although only 8% of these taxa were represented by more than 50 accessions. S. camplyacanthum and Avena vaviloviana (Malz.) Mordv. had the highest number of accessions. Ecogeographical analysis indicated that ELC zones 8, 17, and 18 had the highest frequencies of occurrence in both PAs and genebanks. Complementarity analysis identified 34 potential genetic reserve areas, covering 42 taxa (43%), compared to 33 taxa conserved across 18 PAs identified by coverage analysis. These findings highlight the urgent need for a comprehensive CWR conservation strategy to protect valuable genetic diversity for future crop breeding programs, ultimately enhancing crop resilience in the face of ongoing and future agricultural challenges.